Religious Authority and the Covid 19 Pandemic In South Kalimantan - Noor, Irfan; Khotimah, Husnul; Asiah, Mariatul (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2023)
The response of religious people to the Covid-19 pandemic a few years ago is one of the issues that has attracted the attention of many scholars. This is because many scholars emphasize that the Covid-19 pandemic issue is not only about health issues, but also involves social and religious dimensions. This research is very important to do considering the religiosity of the people of South Kalimantan, where religion is the basis of their daily social life. In this context, researchers want to conduct research with a focus on "Response and Fragmentation of Religious Authority". With this focus, this research wants to explore how the dynamics of religious authorities in South Kalimantan responded to Covid-19 a few years ago in South Kalimantan.